(untitled) (Fiep Bulletin - online, 2016)
Introduction: The development of society leads to changes in lifestyles, with strong changes in consumer eating habits, stimulating the development of packaging technology and achieving a considerable increase in food supply previously prepared, at where, conditions of time and temperature of contact between the product and packaging, are also critical for determining the potential risk of contamination. Objective: Determine the presence of microbial flora in plastic tubes containing mayonnaise, mustard and ketchup, in fixed establishments or street in São Paulo city, and observe the hygiene of the place and food handlers. Methodology: The microbiological analysis was based on Resolution RDC 12, ANVISA, 01/02/2001, using swabs that were passed in the nozzle tubes for sauces (mayonnaise, mustard and ketchup) and placed in support properly identified and transported in cool boxes for the research Institute and Studies on Health São Paulo (IPESSP), for the realization of culture in ready plates, containing Chocolate Agar, Blood Agar, MacConkey Agar, Sabouraud Dextrose Agar, in the temperature of 37°C. To assist in the study, it was made a check list, for verification of good hygiene practices, in accordance with Resolution n°275, Resolution °216 and Portal n° 326. Results: Observed that, among the samples taken from tubes of ketchup, mustard and mayonnaise, the swab method, gave 34% positive, the individual analysis of tubes, obtained the positivity of 18% ketchup, 4% mustard and 12% mayonnaise. Conclusion: The results obtained, it was observed that there is the presence of microbial flora in the tubes of the establishments surveyed, leading to compromised food security, and leading to infectious manifestations. As regards the hygiene of the place and handlers, both were inadequate, contradicting the standards set by ANVISA and the States and Municipalities.